Downregulation of exhausted cytotoxic T cells in gene expression networks of multisystem inflammatory syndrome in children - Noam D. Beckmann (Nature Portfolio, 2021)
Multisystem inflammatory syndrome in children (MIS-C) onsets in COVID-19 patients with manifestations similar to Kawasaki disease (KD). Here the author probe the peripheral blood transcriptome of MIS-C patients to find signatures related to natural killer (NK) cell activation and CD8+ T cell exhaustion that are shared with KD patients.